ANALISIS KEUNGGULAN BERSAING PADA UMKM KOTA SURABAYA - Ayu Endah Wahyudi (AKSELERASI: Jurnal Ilmiah Nasional, 2022)
Most of the factors that cause the competitiveness of MSMEs are still low, namely the quality of MSME human resources is still low, which is influenced by factors of education and managerial knowledge which play a major role in increasing MSME productivity. This study aims to analyze the competitive advantage of SMEs in Indonesia to support the productivity of SMEs in competitiveness. The respondents of this research are business actors in the city of Surabaya. Most of the business actors are managed by women, most of the culinary sector is in great demand by the community and most of the business actors have taken higher education. In addition, the results of this study indicate that business actors can optimize quality products, access suppliers that produce cheap raw materials and skilled business managers. This is expected to be the advantage of SMEs in being competitive.